CREATIVE AND EFFECTIVE STRATEGIES TO ENCOURAGE LEARNERS SPEAKING SKILL IN LARGE CLASSROOMS - Aye, May Zin (PEOPLE: International Journal of Social Sciences, 2018)
This paper purposes at improving of students’ speaking skill in the large classes. One of the biggest issues dealing with schools and teachers today is the management of large classes. It is said that frustrating, noisy and stressful classroom environment cannot easily be overcome. In order to create an effective teaching and learning environment, a class size should be small and a teacher wisely solves to crowded classrooms. Using appropriate and effective teaching methods, teachers not only persuade students’ motivation and interest but also know how to develop learners’ speaking skill. In accordance with the creative and effective ways and strategies discussed in this paper, students get many benefits in the development of speaking skills. This study reveals that creative strategies such as guessing topic, passing a parcel through students, sharing topics, expressing different view supported by a monolingual method in large classrooms, expressed in this paper are useful and effective ways for students to improve their speaking skill as well as for teachers these give benefits when managing large classroom. In brief, these strategies support teachers as effective ways to upgrade the level of students’ speaking skill and attract students to participate in speaking lessons in accordance with students’ response based on a questionnaire.